2023
DOI: 10.3389/fpsyg.2022.1030790
|View full text |Cite
|
Sign up to set email alerts
|

Gamification in EFL/ESL instruction: A systematic review of empirical research

Abstract: IntroductionThis systematic review aims to present the characteristics of the recent research in gamified EFL/ESL instruction, benefits and drawbacks of using gamification in EFL/ESL instruction, and gamification elements.MethodsThe researchers carried out database search in both Web of Science and the Scopus for relevant articles using 15 related key terms. Finally, forty journal articles aligned with the inclusion criteria.ResultsThe results found that gamification has been widely utilized in more than ten n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 73 publications
1
15
0
1
Order By: Relevance
“…As to the limitations of use, Lim and Yunus's (2021) and Singh et al's (2020) results coincide with the findings in this study: The Internet and technology issues were the most prominent external negative factors when implementing gamification, and teachers' skills and interest were the most voiced internal negative factors, especially among senior teachers. Also Dehghanzadeh and Dehghanzadeh (2020) and Zhang and Hasim (2023) identified similar issues, with the majority of the studies reporting the Internet, logistics, and insufficient technology as the main challenges of using gamification platforms.…”
Section: Satisfaction With Applicabilitymentioning
confidence: 80%
See 1 more Smart Citation
“…As to the limitations of use, Lim and Yunus's (2021) and Singh et al's (2020) results coincide with the findings in this study: The Internet and technology issues were the most prominent external negative factors when implementing gamification, and teachers' skills and interest were the most voiced internal negative factors, especially among senior teachers. Also Dehghanzadeh and Dehghanzadeh (2020) and Zhang and Hasim (2023) identified similar issues, with the majority of the studies reporting the Internet, logistics, and insufficient technology as the main challenges of using gamification platforms.…”
Section: Satisfaction With Applicabilitymentioning
confidence: 80%
“…This coincides with Dehghanzadeh et al's (2019) and Singh et al's (2020) conclusions, as both identified several studies that reported positive outcomes of gamification on learners' motivation and engagement. Zhang and Hasim's (2023) systematic review revealed that both learners and teachers held a positive attitude toward gamification mainly because of its capabilities to increase learners' motivation and stimulate their interest and engagement in learning English. Al-Dosakee and Ozdamli (2021) and Kaya and Sagnak (2022) presented similar findings, as they reported a positive effect on learners' motivation, engagement, and overall enjoyment.…”
Section: Perceived Effect On Motivationmentioning
confidence: 99%
“…Thus, the task could be successfully implemented following the introduction of the target structure(s) rather than prior to establishing a basic understanding of that structure. Incorporating a syntactic guessing game in L2 lessons and textbooks has the potential of gamifying L2 syntactic learning and in turn boosting engagement, resulting in improved learning ( Castillo-Cuesta, 2020 ; Sadeghi et al, 2022 ; Zhang and Hasim, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Following these literatures, gamification in our research contexts refers to the incorporation of game design elements into the fitness apps while retaining its instrumental functions for promoting or supporting users’ physical activity/exercise. As an emerging design approach, gamification has attracted a large stream of researches in various contexts, including fitness/health/exercise ( Cheng, 2020 ; Whelan and Clohessy, 2020 ; Yang and Li, 2021 ; Li et al, 2023 ), education ( Sánchez Prieto et al, 2021 ; Behl et al, 2022 ; Chen and Liang, 2022 ; Ghai and Tandon, 2023 ; Oliveira et al, 2023 ; Zhang and Hasim, 2023 ), marketing ( Zhang et al, 2021 ; Wu and Santana, 2022 ), sustainable consumption ( Mulcahy et al, 2020 ), online community ( Xi and Hamari, 2019 ).…”
Section: Literature Review and Theoretical Foundationsmentioning
confidence: 99%